JENIS NEMATODA YANG DITEMUKAN PADA TANAMAN BAWANG MERAH (Allium ascalonicum) DAN RHIZOSFER SEKITARNYA DI AREA PERSAWAHAN NITEN, BANTUL, YOGYAKARTA - Heri Prabowo (Universitas Trunojoyo Madura, 2012)
Constraints in the development of onion plants are plant parasitic nematodes attack. The damage could reach 30% or greater. This study aims to determine the type of plant parasitic nematodes found in onion crops in the area and the surrounding onions fields rhizosfer at Niten, Bantul, Yogyakarta. Isolation of nematodes from roots and leaf tissues of onion used the method of Method Spray funnel and isolation from soil using a modified Baermann funnel. Samples of soil, roots and leaves of onion taken at random from five different locations, each location 20 samples taken. Isolation results are stored in a bottle. Identification of nematodes using identification book Pictorial Key to Genera of Plant Parasitic nematodes. From the results obtained from samples of soil nematodes and roots.Nematodes obtained which consists of four species of Meloidogyne sp., Helicotylenchus sp., Scutellonema sp., and Saprofage sp. Nematodes recovered from soil samples consisted of three species, namely: Helicotylenchus sp., Scutellonema sp., and Saprofage sp . While the roots are found from the sample is composed of two species: Meloidogyne sp. and Saprofage sp .. From these results which are parasitic Meloidogyne sp., Helicotylenchus sp., and Scutellonema sp. while Saprofag sp. not parasitical.